Heterogeneity of Fibroblasts and Myofibroblasts in Pulmonary Fibrosis - Habiel, David M. (Curr Pathobiol Rep, 2017)
PURPOSE OF REVIEW: Idiopathic Pulmonary Fibrosis (IPF) is the most common form of interstitial lung diseases of unknown eathiopathogenesis, mean survival of 3-5 years and limited therapeutics. Characterized by a loss of alveolar type II epithelial cells and aberrant activation of stromal cells, considerable effort was undertaken to characterize the origin and activation mechanisms of fibroblasts and myofibroblasts in IPF lungs. In this review, the origin and contribution of fibroblast and myofibroblasts in lung fibrosis will be summarized. RECENT FINDINGS: Lineage tracing experiments suggested that interstitial lung fibroblasts and lipofibroblasts, pericytes and mesothelial cells differentiate into myofibroblasts. However, epithelial and bone marrow derived cells may give rise to collagen expressing fibroblasts but do not differentiate into myofibroblasts. SUMMARY: There is great heterogeneity in fibroblasts and myofibroblasts in fibrotic lungs. Further, there is evidence for the expansion of pericyte derived myofibroblasts and loss of lipofibroblasts and lipofibroblast derived myofibroblasts in IPF.